Resveratrol toxicity: Effects on risk factors for atherosclerosis and hepatic oxidative stress in standard and high-fat diets - Rocha, K. K. R. [UNESP]; Souza, G. A. [UNESP]; Ebaid, Geovana Xavier [UNESP]; Seiva, F. R. F. [UNESP]; Cataneo, A. C. [UNESP]; Novelli, E. L. B. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2009)
The beneficial action of moderate wine consumption is increasingly being attributed to resveratrol (trans-3,4',5-trihydroxystilbene). To test the safety of resveratrol use as a dietary supplement, 24 mate Wistar rats were initially divided into three groups: (C, n = 6) was given standard chow and water; (R. n = 6) received standard chow and 6 mg/l resveratrol in its drinking water (1 mg/kg/day), and (HFD, n = 12) received high-fat diet and water. In order to more appropriately study the effects of resveratrol on high-fat diet, after 30 days of treatments, HFD-rats were divided into two subgroups (n = 6/group):(HFD) remained receiving high-fat diet and water: (HFD-R) given high-fat diet and 6 mg/l resveratrol in its drinking water (11 mg/kg/day). The total experimental period was 45 days. The resveratrol dose took into account its average concentration in wine, the time variability of wine ingestion, and so of resveratrol consumption in humans. HFD-rats had hyperglycaemia, dyslipidemia, increased serum oxidized-LDL (ox-LDL) and hepatic oxidative stress. Comparing HFD-R and HFD-rats, resveratrol improved lipid profile and glucose level, enhanced superoxide dismutase, thus reducing ox-LDL and hepatic oxidative stress. Resveratrol, in standard-fed-rats reduced glutathione-antioxidant defense system and enhanced hepatic lipid hydroperoxide. In conclusion, based on the results of this single dose preliminary study with resveratrol in the drinking water of male Wistar rats for 30 days, it may be concluded that resveratrol may have beneficial effects in high-fat diets (e.g. ox-LDL, decreased serum and hepatic oxidative stress), but not in standard-fed diets (effects produced include enhanced hepatic oxidative stress). Further studies are indicated. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Resveratrol; Liver; Oxidative stress; Oxidized-LDL; High-fat diet